“Teaching English Language to Students with Down Syndrome” - Saavedra Charcopa, Venus Terersa (2024)
The main objective of this qualitative research was to describe the teaching and learning process of a pre-service English teacher and a student with Down Syndrome employing the Audio-Lingual Method in a rural public school in Pujilí-Cotopaxi during the academic year 2023-2024. This study was applied using the action research method. Data were collected using the teacher's journal, student survey, and observation file. The main findings regarding the teaching experiences with the Audio-Lingual Method showed that the pre-service teacher had difficulties in the first class to execute the lesson plans since the activities were not appropriate to the needs of the student, however, with The implementation of techniques based on the aforementioned method and teaching resources adapted to the girl with Down Syndrome, it was possible to obtain significant results such as the production of short sentences based on the topics covered. These results indicate that the use of the Audio-Lingual method facilitates the learning of students with Down Syndrome since it uses techniques that address the needs of these students such as short-term memory and pronunciation problems.